2003
DOI: 10.1590/s0102-76382003000100014
|View full text |Cite
|
Sign up to set email alerts
|

Surgical treatment of isolated fistulae of coronary arteries

Abstract: Objective: To report the surgical results obtained with the surgical correction of fistulae of coronary arteries in the pulmonary artery branch.Method: From 1995 to 1999, three female patients with diagnoses of isolated fistulae of coronary arteries confirmed by cinecoronariography underwent surgery.Results: No other associated heart diseases were observed in the patients. The main symptom of all patients was angina pectoris. After closing the coronary fistulae the patients progressed with event-free post-oper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 20 publications
1
0
0
Order By: Relevance
“…There still remains a dispute for the surgical treatment of asymptomatic patients. Our study showed that surgical treatment of CAVFs when coexisting with other cardiac diseases is a safe procedure with low mortality and morbidity in accordance with the literature [3,7,8,10,14,19] . Thus, operating asymptomatic adult patients with low mortality and morbidity may reduce or eliminate the risk of subsequent development of complications such as myocardial infarction.…”
Section: Discussionsupporting
confidence: 90%
“…There still remains a dispute for the surgical treatment of asymptomatic patients. Our study showed that surgical treatment of CAVFs when coexisting with other cardiac diseases is a safe procedure with low mortality and morbidity in accordance with the literature [3,7,8,10,14,19] . Thus, operating asymptomatic adult patients with low mortality and morbidity may reduce or eliminate the risk of subsequent development of complications such as myocardial infarction.…”
Section: Discussionsupporting
confidence: 90%